Combined effect of thyme and clove phenolic compounds on Xanthomonas campestris pv. campestris and biocontrol of black rot disease on cabbage seeds - Hakalová, Eliška; Čechová, Jana; Tekielska, Dorota A.; Eichmeier, Ales; Pothier, Joël F. (Frontiers in Microbiology, 2022)
The seed-borne bacterium Xanthomonas campestris pv. campestris (Xcc) as a causal organism of black rot disease remains the most serious bacterial problem of agricultural production of cruciferous plants worldwide. The eradication of a primary inoculum originating in seeds is available, but no treatment is totally effective. With the threat of developing chemical resistance and increasing pressure for sustainable disease management, biocontrol methods represent one of the main strategies currently applied in agriculture. Natural antimicrobials, including essential oils, are promising tools in disease management with low risks of environmental pollution and impact on human health. Thyme and clove essential oils were demonstrated to be highly effective in Xanthomonas studies in vitro; therefore, their application in black rot control was evaluated in this study. From five phenolic substances originating from thyme and clove essential oils (carvacrol, eugenol, linalool, p-cymene and thymol), the most promising in vitro results were observed with carvacrol, for which 0.0195% led to the death of all Xcc cells in 30 min. Moreover, a synergistic antibacterial effect of carvacrol and thymol solutions decreased the minimal inhibition concentration to 0.0049% and 0.0195% for carvacrol and thymol, respectively. Using the quadruple bactericidal values, the complete elimination of Xcc from the surface of infested cabbage seeds was obtained for both carvacrol and thymol solutions and their combined mixture at 2 MIC value. The elimination of bacterial infection from germinated cabbage plants was observed for both plate counting and quantitative real-time PCR methods. We also evaluated the effect of the application of phenolic treatment on the seed germination and germinated plants. Our results suggest a high potential of the application of carvacrol and thymol in vegetable seed production, specifically for cabbage, thus representing a suitable alternative to cupric derivatives.